Application of optimisation methods for quantum sensors and gravity surveys - Petrucci, Claudia (2018)
The aim of this study is the use of optimisation methods both for the design of the components of quantum gravity sensors and for the investigation of optimum gravity surveys to collect data for geophysical exploration. The first part of the thesis is focused on the optimisation of a gravity survey. An optimised acquisition scheme is designed using the content coming from the horizontal gravity gradients. The data acquired with this "optimised grid" and with a regular grid are inverted and the performances of the different schemes are analysed through the comparison of their model resolution matrices. It is proved that the "optimised grid" allows a higher resolution than the regular grid in the proximity of the gravity anomaly to detect. The second part of the thesis is dedicated to the design of a magnetic trap with Comsol Multiphysics software and to the numerical modeling of a magneto-optical trap. The parameters used to design the magnetic trap are inferred from an optimisation method specifically conceived to miniaturise the dimensions and diminish the power consumption of the device. The Comsol Multiphysics software is used to verify the magnetic field, the heating, stress, strain and temperature produced by such a device. Moreover, in order to integrate the magnetic trap with optical access to build an optimum Magneto-Optical Trap (MOT), a numerical model of a 3D MOT that takes into account realistic effects (e.g. multiple level of atoms, Gaussian profile of the beams) is tested. This represents the initial step of an optimisation method that could allow the realisation of optimum MOTs.